Prices versus Quantities Reassessed - Larry S. Karp; Christian P. Traeger (Center for Economic Studies and ifo Institute (CESifo), 2018)
“Prices versus quantities” (Weitzman 1974), a hugely influential paper, is widely cited (and taught) in current debates about the best policy to reduce greenhouse gas emissions. The paper's criterion for ranking policies suggests that technological uncertainty favors taxes over cap and trade. Weitzman models a flow pollutant, but greenhouse gases are persistent. Stock pollutants require a fundamental change in the ranking criterion. Innovations' persistence and their gradual diffusion both favor the use of cap and trade. Numerical results show that the case for cap and trade as a means of reducing greenhouse gas emissions is stronger than widely believed.
Keywords: Q00; Q50; H20; D80; 330; policy instruments; pollution; climate change; taxes; quantities; regulation; uncertainty; cap and trade; technology